Conservation Easements: Design Flaws, Enforcement Challenges, and Reform (Utah Environmental Law Review; Vol 33 No 1 (2013), 2014)
The conservation easement is exceptional. As a property right, it is a creature of modern invention, a curiosity not recognized at common law. Initially, courts were reluctant to validate this negative, in-gross easement. It hinders alienability, may be perpetual, and is owned in absentia, not appurtenant to the restricted land. In part for these reasons, the Uniform Conservation Easement Act was needed to rescue the conservation easement from an uncertain future and give it legitimacy. Still, the conservation easement might have been merely a limited development in the law of real property but for the federal income tax laws.